Evaluation of the Formulation of Combined Dosage Form of Albendazole and Mebendazole through In vitro Physicochemical and Anthelmintic Study - Fatema, Kaniz; Sajeeb, BK; Sikdar, KM Yasif Kayes; Hossain, ASM Monjur Al; Bachar, Sitesh C (Dhaka University Journal of Pharmaceutical Sciences, 2022)
In the current study, the combination of albendazole and mebendazole was analyzed as a potential anthelmintic agent against Lumbricus terrestris (commonly known as earthworms). The in vitro analysis showed the combination of 400 mg albendazole and 300 mg mebendazole had more significant therapeutic activities (mean paralysis time 58 minutes and mean death time 97.33 minutes) than the others. Then the combinations were formulated as tablet using different ratios of excipients where formulation-D performed excellent flow properties (Carr’s index: 14.04±0.27, Hausner’s ratio: 1.19 ± 0.03, Angle of repose: 40.22 ± 0.73). The dosage form prepared from formulation-D had better hardness of 9.40 ± 0.34 kg-N and loss of weight of 0.003 mg compared to other formulations. In terms of disintegration and dissolution studies, formulation-D exhibited excellent properties. The tablet was disintegrated fully within 8.94 ± 0.37 minutes in phosphate buffer (pH 8.3) and dissolution analysis showed R2 of 0.995 for albendazole and 0.991 for mebendazole which were statistically significant. The postformulation anthelmintic study showed that the prepared tablet dosage form was therapeutically effective because it paralyzed and killed all the earthworms within 56 and 85 minutes, respectively. Finally, the tablet was subjected to the scanning electron microscopy (SEM) analysis which confirmed better surface morphology and drug-drug compatibility within the dosage form. The next stage of the work will focus on in vivo analysis for market preparation. Dhaka Univ. J. Pharm. Sci. 21(2): 153-163, 2022 (December)